Atomic Force Microscopy on Biological Materials Related to Pathological Conditions. (12th May 2019) - Stylianou, Andreas; Kontomaris, Stylianos-Vasileios; Grant, Colin; Alexandratou, Eleni
Abstract : Atomic force microscopy (AFM) is an easy-to-use, powerful, high-resolution microscope that allows the user to image any surface and under any aqueous condition. AFM has been used in the investigation of the structural and mechanical properties of a wide range of biological matters including biomolecules, biomaterials, cells, and tissues. It provides the capacity to acquire high-resolution images of biosamples at the nanoscale and allows at readily carrying out mechanical characterization. The capacity of AFM to image and interact with surfaces, under physiologically relevant conditions, is of great importance for realistic and accurate medical and pharmaceutical applications. The aim of this paper is to review recent trends of the use of AFM on biological materials related to health and sickness. First, we present AFM components and its different imaging modes and we continue with combined imaging and coupled AFM systems. Then, we discuss the use of AFM to nanocharacterize collagen, the major fibrous protein of the human body, which has been correlated with many pathological conditions. In the next section, AFM nanolevel surface characterization as a tool to detect possible pathological conditions such as osteoarthritis and cancer is presented. Finally, we demonstrate the use of AFM for studying other pathological conditions, such as Alzheimer's disease and human immunodeficiency virus (HIV), through the investigation of amyloid fibrils and viruses, respectively. Consequently, AFM stands out as the ideal research instrument for exploring the detection of pathological conditions even at very early stages, making it very attractive in the area of bio- and nanomedicine.